On translation, creativity and students’ perception around the assistance provided by AI - Recuenco-Peñalver, María (My University, 2024)
First year students of the Translation and Interpreting Degree at the University of Malaga (Spain) register for a compulsory course titled “Computer resources applied to Translation and Interpreting”. The subject is divided into four modules, of which the first three are devoted to developing and mastering computer literacy, while the fourth one (lasting four weeks out of the 15 weeks module) is specifically designed around theory and practice of automatic translation and computer-assisted translation tools. For most of the students, that is the first time they get exposed to the above concepts. Using a survey at the beginning of the module and a different one at the end of it, it is our intention to being able to draw conclusions on student’s perceptions regarding the use of technology when translating. We shall also try and make them think about the relationship between the use of technology and the impact that it can have on their own creativity and skills when translating. Finally, we shall suggest ways to make use of AI in the Translation classroom in order to find ways to challenge students to use it in a creative way.
Keywords: Traducción - Innovaciones tecnológicas - Congresos; Interpretación; Creatividad; Inteligencia artificial; Didáctica